Digital Comic "My Dream is My Motivation" as a Group Guidance Medium to Increase Learning Motivation - Agus Dwiyanturi; Budi Astuti (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
This study aims to determine the feasibility, practicality, and effectiveness of the My Dreams is My Motivation Digital Comic as a group guidance medium to increase learning motivation in junior high school students. This study uses the R&D method with the ADDIE development model. The subjects in this study were 2 guidance and counseling teachers and 6 students in the initial field trial. The operational group test consisted of 40 students. Data collection techniques and instruments used a media feasibility test scale, a material feasibility test scale, a guidance and counselling teacher response questionnaire, a student response questionnaire, and a learning motivation scale. The results of this study show that 1) Digital Comics Eligibility for “My Dreams is My Motivation”, according to media experts, was categorised as "very feasible" with a percentage of 4.15%, the assessment of material experts was categorised as "very feasible" with a percentage of 4.36%; 2) Practicality of Digital Comics “My Dreams is My Motivation." According to teachers, guidance and counselling are categorised as "very practical" with a percentage of 4.36%; 3) Digital Comic Effectiveness “My Dreams is My Motivation” is very effective in increasing students motivation to learn.